War-time memories and fairy tales - Lampe, Urška (Annales. Series historia et sociologia, 2023)
This contribution explores the story of Angelo, an Italian Second World War veteran who, after experiencing war and escaping captivity in Yugoslavia, finally reached Trieste in 1946, where he met his future wife. It took him nearly 15 years to heal from his harrowing wartime trauma. Between 2021 and 2023, while collecting oral testimonies, I interviewed his son Sergio and grandson Ruben. The central subject of those interviews was the war-time period and the fairy tales that Angelo used to tell his son (and later his grandson) in the evenings, inspired by his war experiences. By recounting his war experiences in a metaphorical and child-friendly manner, these tales were not only imaginative and captivating for the child, but also served a profound purpose: they were (1) a way to communicate his memories and experience to the following generations; (2) a means to cope with his experiences and past; (3) a tool to socialise and educate his son, transmitting moral norms, social memories and preparing him for life in society.
Keywords: druga svetovna vojna; fairy tales; Jugoslavija; medgeneracijski prenos spomina; pravljice; prisoners of war; second world war; socialisation; socializacija; transgenerational transmission of memory; trauma; travme; vojni ujetniki; Yugoslavia